Autoridade médica e divulgação científica no Grão-Pará flagelado pelo cólera: século XIX - BELTRÃO, Jane Felipe (2013)
The increment of the Cholera epidemic in 1855 in Grão-Pará started a strong debate among the doctors of the Province regarding the conduct and treatment for the sick. Besides the academic discussion, therapeutical information was largely published in the local press. The documents appearing in the newspapers reveal a pedagogical and persuasive nature. In the Grão-Pará, voices of such nature were heard in the Treze de Maio and in the Diario do Gram Pará. in Rio, the capital of the Empire at the time, the debate took place in the pages of Jornal do Commercio and the Diario do Rio de Janeiro. The paper presents the efforts of science writing based on medical authority of the professionals at work during the Cholera epidemis in Grão-Pará.